Effects of transcranial direct current stimulation on working memory and negative symptoms in schizophrenia: a phase II randomized sham-controlled trial - J.S. Gomes; A.P. Trevizol; D.V. Ducos; A. Gadelha; B.B. Ortiz; A.O. Fonseca; H.T. Akiba; C.C. Azevedo; L.S.P. Guimaraes; P. Shiozawa; Q. Cordeiro; A. Lacerda; et al. (Schizophrenia Research: Cognition, 2018)
Background: The lack of efficacy of pharmacological treatments for cognitive and negative symptoms in schizophrenia highlights the need for new interventions. We investigated the effects of tDCS on working memory and negative symptoms in patients with schizophrenia. Method: Double-blinded, randomized, sham-controlled clinical trial, investigating the effects of 10 sessions of tDCS in schizophrenia subjects. Stimulation used 2 mA, for 20 min, with electrodes of 25 cm2 wrapped in cotton material soaked in saline solution. Anode was positioned over the left DLPFC and the cathode in the contralateral area. Twenty-four participants were assessed at baseline, after intervention and in a three-months follow-up. The primary outcome was the working memory score from MATRICS and the secondary outcome the negative score from PANSS. Data were analyzed using generalized estimating equations. Results: We did not find group ∗ time interaction for the working memory (p = 0.720) score or any other cognitive variable (p > 0.05). We found a significant group ∗ time interaction for PANSS negative (p < 0.001, d = 0.23, CI.95 = −0.59–1.02), general (p = 0.011) and total scores (p < 0.001). Exploratory analysis of PANSS 5 factors suggests tDCS effect on PANSS negative (p = 0.012), cognitive (p = 0.016) and depression factors (p = 0.029). Conclusion: The results from this trial highlight the therapeutic effects of tDCS for treatment of persistent symptoms in schizophrenia, with reduction of negative symptoms. We were not able to confirm the superiority of active tDCS over sham to improve working memory performance. Larger sample size studies are needed to confirm these findings.